2019
DOI: 10.1016/j.icarus.2018.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Age of martian air: Time scales for martian atmospheric transport

Abstract: A B S T R A C TThe mean time since air in the Martian atmosphere was in the low-latitude boundary layer is examined using simulations of an idealized "mean age" tracer with the MarsWRF general circulation model. The spatial distribution and seasonality of the mean age in low-and mid-latitudes broadly follow contours of the mean meridional circulation, with the mean age increasing from 0 at the surface to a maximum of 60-100 sols in the upper atmosphere. Substantially older mean ages (exceeding 300 sols) are fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…Global uniform mixing of methane occurs on a scale of 2 to 3 months 6,8,23 . Even in the extremely unlikely case where Gale Crater would constitute the sole source of methane on Mars (note that Gale Crater and surrounding areas along the Martian dichotomy host geological features where methane could be released 13 ), MSL measurements still remain in disagreement with the detection limits derived from TGO measurements.…”
Section: The Detection Of Methane On Mars Has Been Interpreted As Indmentioning
confidence: 99%
“…Global uniform mixing of methane occurs on a scale of 2 to 3 months 6,8,23 . Even in the extremely unlikely case where Gale Crater would constitute the sole source of methane on Mars (note that Gale Crater and surrounding areas along the Martian dichotomy host geological features where methane could be released 13 ), MSL measurements still remain in disagreement with the detection limits derived from TGO measurements.…”
Section: The Detection Of Methane On Mars Has Been Interpreted As Indmentioning
confidence: 99%
“…The difference in particle size between the initiation of the polar hood cloud and its dissipation suggests that the microphysical environment within the polar region changes as the fall and winter seasons progress, although the CRISM observations cannot directly inform us of the microphysical processes. Waugh et al () noted that the lower (0–20 km) winter polar atmosphere mixes with the lower latitude atmosphere on short (approximately tens of sols) timescales even during midwinter, suggesting that there should be a steady flux of ice nuclei (in the form of dust) into the polar atmosphere. Perhaps this effect, combined with the atmosphere mixing generated by CO 2 convection and precipitation (e.g., Hayne et al, , Kuroda et al, ), serves to create an equilibrium in the polar atmosphere to create the fairly uniform 1.5‐μm profile with altitude observed at the end of winter.…”
Section: Resultsmentioning
confidence: 99%
“…Recent results from the Trace Gas Orbiter's (TGO) Atmospheric Chemistry Suite and Nadir and Occultation for Mars Discovery instruments onboard ExoMars have now provided a robust upper limit on methane in the atmosphere above 5 km of <50 pptv (Korablev et al, ) with values below 12 pptv observed at clear northern latitudes down to 3 km above the surface. This upper limit, in turn, places a strong constraint on the methane content of the bulk of the Martian atmosphere through the vigorous atmospheric mixing thought to occur on Mars, based on atmospheric models (Waugh et al, ). Indeed, Korablev et al () correctly point out that when combining together (1) the ~1‐sol daytime mixing timescale required for the air within Gale crater to mix with outside air (Moores et al, ; Rafkin et al, ) with (2) persistent values measured within Gale that average ~410 pptv and (3) the ~300‐year expected photochemical lifetime of methane on Mars (Atreya et al, ), that the flux of methane out of Gale crater should be approximately 30 kg/sol or 6 × 10 −4 tonnes·km −2 ·year −1 (Korablev et al, ), 20 times higher than the estimate of Moores et al ().…”
Section: Introductionmentioning
confidence: 99%